2015
DOI: 10.1016/j.chemgeo.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing magnesite formation at low temperature and high CO2 pressure: The impact of seed crystals and minor components

Abstract: The formation of magnesite was followed in aqueous solution containing initially added Mg(OH) 2 equilibrated with supercritical carbon dioxide (90 atm pressure, 50°C) in the presence of introduced magnesite particles and minor components, Co(II). As expected, the introduction of magnesite particles accelerated the formation of magnesite from solution. However, the formation rate of magnesite was even greater when small concentrations of Co(II) were introduced, indicating that the increased rate of magnesite fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Since the development of laser‐assisted APT, there has been growing interest in applying nanoscale geochemical characterisation to a broad range of geological materials including glass (Gin et al , Hellmann et al , Gin et al ), diamond (Heck et al , Lewis et al , Schirhagl et al , Mukherjee et al ), Fe‐Ni metal alloys (Einsle et al ) and silicides (Gopon et al ), platinum‐group alloys (Parman et al , Daly et al , ), oxides (Bachhav et al , , Fahey et al , Taylor et al , Frierdich et al , Gamal El Dien et al , Genareau et al , Taylor et al ), carbonates (Felmy et al , Branson et al , Pérez‐Huerta et al , Pérez‐Huerta and Laiginhas ), sulfides (Fougerouse et al , Dubosq et al , Fougerouse et al , Gopon et al , Wu et al ), sulfates (Weber et al ), zeolites (Schmidt et al ) and rock‐forming silicates, such as feldspars (White et al , Cao et al ) and olivine (Bloch et al , Cukjati et al , Figure ). However, a high proportion of the published APT work to date has focussed on trace element mobility, particularly Pb, in accessory minerals.…”
Section: Geoscience Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the development of laser‐assisted APT, there has been growing interest in applying nanoscale geochemical characterisation to a broad range of geological materials including glass (Gin et al , Hellmann et al , Gin et al ), diamond (Heck et al , Lewis et al , Schirhagl et al , Mukherjee et al ), Fe‐Ni metal alloys (Einsle et al ) and silicides (Gopon et al ), platinum‐group alloys (Parman et al , Daly et al , ), oxides (Bachhav et al , , Fahey et al , Taylor et al , Frierdich et al , Gamal El Dien et al , Genareau et al , Taylor et al ), carbonates (Felmy et al , Branson et al , Pérez‐Huerta et al , Pérez‐Huerta and Laiginhas ), sulfides (Fougerouse et al , Dubosq et al , Fougerouse et al , Gopon et al , Wu et al ), sulfates (Weber et al ), zeolites (Schmidt et al ) and rock‐forming silicates, such as feldspars (White et al , Cao et al ) and olivine (Bloch et al , Cukjati et al , Figure ). However, a high proportion of the published APT work to date has focussed on trace element mobility, particularly Pb, in accessory minerals.…”
Section: Geoscience Applicationsmentioning
confidence: 99%
“…, Hellmann et al 2015, Gin et al 2017, diamond(Heck et al 2014, Lewis et al 2015, Schirhagl et al 2015, Mukherjee et al 2016, Fe-Ni metal alloys(Einsle et al 2018) and silicides(Gopon et al 2017), platinum-group alloys(Parman et al 2015, Daly et al 2017, oxides(Bachhav et al 2011, Fahey et al 2016, Taylor et al 2018, Frierdich et al 2019, Gamal El Dien et al 2019, Genareau et al 2019, Taylor et al 2019, carbonates(Felmy et al 2015, Branson et al 2016, P erez- Huerta et al 2016, P erez-Huerta and Laiginhas 2018, sulfides, Dubosq et al 2019, Gopon et al 2019, Wu et al 2019, sulfates(Weber et al 2016), zeolites(Schmidt et al 2019) and rock-forming silicates, such as feldspars(White et al 2018c, Cao et al 2019) and olivine(Bloch et al 2019, Cukjati et al 2019 …”
mentioning
confidence: 99%
“…Of the minerals studied so far, very good results have been documented for APT analysis of carbonates (McMurray et al 2011, Felmy et al 2015, Pérez-Huerta et al 2016, Pérez-Huerta and Laiginhas 2018, phosphates (Gordon et al 2012, Santhanagopalan et al 2015, La Fontaine et al 2016, DeRocher et al 2020, sulfate and sulfide minerals (Fougerouse et al 2016, Weber et al 2016, Weber et al 2018, oxides (Kuhlman et al 2001, Gordon and Joester 2011, Genareau et al 2019, Taylor et al 2019, Verberne et al 2019 and silicates (Arey et al 2012, Bachhav et al 2015, Valley et al 2015, Exertier et al 2018, White et al 2018, Bloch et al 2019. The application of APT to these minerals has provided significant information for geochronology (Valley et al 2014, Verberne et al 2019, biogeochemistry and biomineralisation (Gordon et al 2012, Branson et al 2016, La Fontaine et al 2016, metamorphism (Peterman et al 2019) and the study of extra-terrestrial materials (Heck et al 2014, Daly et al 2020, Lewis et al 2020.…”
mentioning
confidence: 99%
“…Beyond the pH effect caused by the presence of zinc ions, their strong hydration enthalpy can also play a role in the formation of magnesium carbonate, in particular the dehydration of magnesium ions for incorporation in the dolomite crystal structure, as suggested by Vandeginste et al [7]. Another study showed that the addition of cobalt(II) ions in solution accelerates the formation of magnesite [34]. The latter authors interpreted this effect as a result of the incorporation of cobalt(II) in the magnesite crystal structure [34].…”
Section: Effect Of Zinc Ionsmentioning
confidence: 95%
“…Another study showed that the addition of cobalt(II) ions in solution accelerates the formation of magnesite [34]. The latter authors interpreted this effect as a result of the incorporation of cobalt(II) in the magnesite crystal structure [34]. It is noted here that the hydration enthalpy of cobalt(II) ions (−1996 kJ•mol −1 ) is stronger than that of magnesium ions (−1921 kJ•mol −1 ), which is also the case for zinc ions and one of the underlying reasons behind the study on the effect of zinc ions.…”
Section: Effect Of Zinc Ionsmentioning
confidence: 99%